Bengal Arch kind of roof for the Antarala (antechamber) - Temples of India Project Team (Jio Institute, 2024)
The elongated rectangular Bengal arch kind of roof for the antarala (antechamber). The flat ceiling has a blue floral pattern similar to the cusps of the arches and the curved edges have multi-colour ornamentation. The circular motifs on the curved sides of the arch resemble mirrors which are usually found in colonial period architecture and paintings.